Childhood Visceral Leishmaniasis: Distinctive Features and Diagnosis of a Re-emerging Disease. An 11-year Experience From a Tertiary Referral Center in Athens, Greece. Issue 5 (May 2018) - Krepis, Panagiotis; Krepi, Adamantia; Argyri, Ioanna; Aggelis, Anastasios; Soldatou, Alexandra; Papaevangelou, Vasiliki; Tsolia, Maria
Abstract : Background: Visceral leishmaniasis (VL) remains a public health issue in Greece. The aim of this study was to describe the clinical and epidemiologic characteristics of pediatric VL in our region as well as to evaluate the laboratory findings and the diagnostic techniques that are applied. Methods: We retrospectively reviewed the medical records of all children diagnosed with VL in an 11-year period at a tertiary public hospital in the region of Athens. Demographic features, clinical information and laboratory findings were accessed. Results: A total of 43 cases were recorded during 2005–2015. Median age of the patients was 3.7 years. Pallor (100%), fever (98%), hepatosplenomegaly (55.8%) and appetite loss (32.6%) were the most common presentations of the disease. The predominant laboratory abnormalities were anemia (100%), thrombocytopenia (90.7%), elevated inflammatory markers (86.1%) and decreased albumin/globulin (A/G) ratio (72.1%). Four patients developed secondary hemophagocytic lymphohistiocytosis syndrome, whereas in 3 others abdominal ultrasound showed splenic nodules. Bone marrow aspiration detected Leishmania parasites in 92.7% of cases and the rapid rK39 strip test indicated anti-Leishmania antibodies in 97.1% of children. In addition, all patients in whom indirect immunofluorescent antibody test was implemented had positive results. Conclusions: VL still affects children in our area. Fever, splenomegaly, anemia and appetite loss are the typical findings in children. Noninvasive techniques (immunofluorescent antibody test, rK39) in combination with bone marrow microscopy are useful in the diagnosis of pediatric VL.